Lymphatic Function Decreases over Time in the Arms of Breast Cancer Patients following Treatment. Issue 9 (16th September 2022) - Johannessen, Andreas L.; Alstrup, Mathias; Hjortdal, Vibeke E.; Offersen, Birgitte V.; Mohanakumar, Sheyanth
Abstract : Background: In patients with breast cancer-related lymphedema, distinct lymphatic patterns and changed lymphatic contractile function have been described, but it is unknown how these characteristics change over time and to what extent they appear before clinical edema is detectable. Recently, we described the lymphatic morphology and function in a cohort of breast cancer patients shortly after radiation therapy (RT). In the current study, we investigate lymphatic function and morphology in the same cohort after 1 year of follow-up. Methods: The study population consisted of 28 breast cancer patients investigated 12 months after adjuvant locoregional RT. Lymphatic contraction frequency (CF), propulsion velocity, and the morphology of lymphatic vessels in the upper extremities were described in vivo using near-infrared fluorescence imaging. Lymphatic stress test was performed using hyperthermia. Results: At 1 year after RT, (n = 28) 46% of the patients presented with lymphatic morphological abnormalities with a degree of dermal backflow and 21% had developed clinical breast cancer-related lymphedema. In the ipsilateral arm, CF was 23% lower than in the contralateral arm ( P = 0.04). Since primary examination, CF in the ipsilateral arm decreased by 40% ( P = 0.03), whereas no change was observed in the contralateral arm. During hyperthermia, the ipsilateral arms with lymphatic complications were not able to increase CF as the remaining subgroups. Conclusions: Lymphatic function in the ipsilateral arm deteriorated over time after adjuvant breast cancer therapy. Furthermore, the presence of abnormal torturous lymphatic vessels in asymptomatic arms appeared to be associated with weak lymphatic reserve pumping capacity.